2004
DOI: 10.1038/sj.eye.6701466
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Gender, Body Mass Index, and Axial Length with Central Retinal Thickness Using Optical Coherence Tomography

Abstract: Background Optical coherence tomography (OCT) acquires cross-sectional retinal images with high resolution using low-coherence interferometry. Few studies have studied the effect of demographic data and ocular parameters that may affect central retinal thickness. In this study, these factors were used as parameters to analyse if any significant relationship exists with central retinal thickness. Methods Volunteers with a best-corrected visual acuity of 6/12 or better and no evidence of ocular abnormalities or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
88
6
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(119 citation statements)
references
References 16 publications
24
88
6
1
Order By: Relevance
“…40,41 Lam et al 40 hypothesized that the thicker fovea could be a sign of early vitreoretinal traction in highly myopic eyes. Previous studies reported that women have thinner macular measurements, 13,30,38,39 which is consistent with our results. This may explain why certain macular conditions, such as macular hole, occur more frequently in women.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…40,41 Lam et al 40 hypothesized that the thicker fovea could be a sign of early vitreoretinal traction in highly myopic eyes. Previous studies reported that women have thinner macular measurements, 13,30,38,39 which is consistent with our results. This may explain why certain macular conditions, such as macular hole, occur more frequently in women.…”
Section: Discussionsupporting
confidence: 83%
“…Lastly, macular thickness was assessed by instruments other than the OCT in some of the earlier studies, such as the retinal thickness analyzer, and these imaging modalities may not be comparable to Stratus OCT. 10,29,[35][36][37] We identified age, gender, and SE as factors that significantly affected macular measurements using Stratus OCT, which is consistent with the results of previous studies. 10,13,18,[38][39][40][41] However, our results also indicate that more myopic individuals have an increased foveal thickness but reduced macular volume, which substantiate earlier reports. 40,41 Lam et al 40 hypothesized that the thicker fovea could be a sign of early vitreoretinal traction in highly myopic eyes.…”
Section: Discussionsupporting
confidence: 81%
“…1,[3][4][5]20,21 It has been hypothesized that with increasing myopia and axial length, the thickness of the inner and outer rings of the macula is decreased due to the mechanical stretching of a similar volume of retina over a larger area. 22,23 Congruent with this hypothesis, we found significant positive correlations between outer macula thicknesses and SER, and significant negative correlations between outer macular thicknesses and AL. Similar correlations were also found by other authors.…”
Section: Macular Thicknesssupporting
confidence: 59%
“…16 Therefore, we compared the differences of the macular and RNFL thicknesses between men and women. In the normal participants, the macula was thinner in women than in men but the difference was not significant.…”
Section: Eyementioning
confidence: 99%